Reagent Stock Prediction Using Monte Carlo Method At Populer Clinical Laboratory Surabaya - Farah Dibba; Wiwiet Herulambang; Fardanto Setyatama (Fakultas Teknik Universitas Bhayangkara, 2022)
Prediction is important as decision are made earlier. Information are needed before prediction is optimallydone. Company operational supply can be predicted and depicted in computerized process. By doing so, a decisionbased on past probabilities could be made efficiently. In the simulation, stock of goods is important. Reagent stockprediction could be done by using Monte Carlo method. Monte Carlo method is one of a tool that can be used toanalyze common uncertainty in reagent stock procurement. The result of Monte Carlo prediction can help companyto determine the future amount of reagent stock. In this research, the forecast results 95,83% accuracy by using 2022annual stock data.